Aviation and the environment in the context of the EU-US open skies agreement - Karen Mayor; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2008)
We examine the impacts of the EU-US Open Skies agreement on the environment, in particular looking at the effect of the agreement on emissions from the aviation sector. We use the Hamburg Tourism Model, a model of domestic and international tourist numbers and flows, to estimate these impacts. The Open Aviation Area will result in increased competition between carriers and consequently falls in the cost of transatlantic flights. This will not only have implications for the size and structure of the industry but also for climate policy. The objectives of this paper are (1) to assess what effects the expected increases in passenger numbers will have on CO2 emissions and (2) to test whether this increase in travel will result in a corresponding rise in emissions. Model simulations show that passenger numbers arriving from the US to the EU will increase by between 1% and 14% depending on the magnitude of the price reductions. We find that because of substitution between destinations, the percentage increase in global emissions is much smaller (max. 1%) than the increase in cross-Atlantic traffic. In the current context of greenhouse gas control policies, any increase in emissions will make climate policy objectives more difficult to achieve and will attract more attention to aviation's contribution to climate change.
Keywords: 330; international tourism; open skies agreement; carbon dioxide emissions; climate policy; externalities; Tourismus; Luftverkehr; Internationales Abkommen; Umweltpolitik; Umweltbelastung; Kohlendioxid; USA; EU-Staaten